ANALISIS TINGKAT EFISIENSI BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) PERIODE 2012-2018 MENGGUNAKAN METODE DATA ENVELOPMENT ANALYSIS (DEA) - Septiani, Erika; Rani, Lina Nugraha (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
The purpose of this study was to determine the level of efficiency of Islamic People's Financing Banks (Sharia Rural Banks) registered at the OJK during the 2012-2018 period. This study uses a quantitative approach. The data used are secondary data in the form of annual financial reports obtained from the websites of Bank Indonesia (BI) and the Financial Services Authority (OJK). This study uses a non-parametric approach to measure the stability of the level of efficiency of the Islamic People's Financing Bank (BPRS) with the Data Envelopment Analysis (DEA) method. The results of this study indicate that under the CRS assumption with an output-oriented average efficiency of the Islamic People's Financing Bank (BPRS) for the 2012-2018 period is 79 percent, while under the assumption of the output-oriented VRS the average efficiency of the Islamic People's Financing Bank (BPRS) is 85 percent which means that the Islamic People's Financing Bank during the 2012-2018 period still operates inefficiently. BPRS Harta Insan Karimah Parahyangan became the only Sharia People Financing Bank (BPRS) in Indonesia for the 2012-2018 period that was the most stable both under the VRS assumption.Keywords: Stability, Intertemporal Efficiency, Data Envelopment Analysis, Islamic Rural BankREFFERENCESArikunto, S. 2002. Metodologi Penelitian Suatu Pendekatan Proposal. Jakarta: PT. Rineka Cipta.Barzan, Bardawi. 1999. Psikologi Perkembangan Anak..Jakarta: Rineka Cipta.Chaplin,J.P. 1996. Kamus Besar Psikologi. Jakarta: Rajawali PressDepartemen Agama RI. 1993. Al-Qur’an Dan Terjemahannya.Departemen Sosial RI. 1999. Pedoman Perlindungan Anak. Jakarta: Direktorat Jendral Bina Kesejahteraan Sosial Anak Keluarga dan Lanjut UsiaMoleong,L.J.2010. Metodologi Penelitian Kualitatif. Bandung: Remaja Rosdakarya.Parker, Deborah,.2006. Menumbuhkan Kemandirian dan Harga Diri Anak. Jakarta: Prestasi PustakarayaSugiyono. 2012. Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung: Alfabeta.Yin, Robert. K, 2009, Studi Kasus; Desain dan Metode, Jakarta; Raja Grafindo Persada.Tjiptono, Fandy. 2006. Strategi Pemasaran. Yogyakarta: Andi Offset.Kotler, Philip. 2000. Manajemen Pemasaran di Indonesia: Analisis, Perencanaan, implementasi dan Pengendalian. Alih Bahasa, Susanto, A.B. Jakarta: Penerbit Salemba EmpatRangkuti,Freddy. 2013. Analisis SWOT : Teknik Membedah Kasus Bisnis. Jakarta : PT. Gramedia Pustaka UtamaUndang-Undang Nomor 23 Tahun 2002 tentang Perlindungan AnakDepartemen Sosial Republik Indonesia. 2004. Acuan Pelayanan Sosial Anak di Panti Sosial Asuhan Anak. Jakarta : Departemen Sosial Republik Indonesiawww.bps.go.id Ridwan S. Sundjaja dan Inge Barlian, 2002. Manajemen Keuangan Satu Edisi Keempat. Jakarta: Prenhallindo.Pearce II, John A. dan Robinson Richard B.Jr. 2008. Manajemen Strategis 10. Jakarta: Salemba Empat.Tarmidzi, Rosmiaty. 2010. Pendapatan Asli Daerah Berdampak Pada Kemandirian Keuangan Daerah. Jurnal Akuntansi dan Keuangan Vol. 1 No.1 Hal. 123-128.Halim, Abdul. 2007. Akuntansi Keuangan Daerah. Jakarta: Salemba Empat. Halim, Abdul. 2002. Manajemen Keuangan Daerah Bunga Rampai. Yogyakarta: UPP AMP YKPN Yogyakarta.